Communication without borders in times of Pandemics The Enlazadas Project by the Network of Latin American and Caribbean Publishers, EULAC - Soto-Ramírez, Marybel (2022)
This article presents an approach to Latin American publishing networks, their role and importance and how, through joint work, the dissemination of knowledge generated by the academic press is expedited. To exemplify this process, the Enlazadas project of the EULAC Latin American and Caribbean Publishing Network is analyzed and how it has enriched the dissemination and networking process in the context of the Covid-19 pandemic